Redheaded Pine Sawfly Neodiprion lecontei (Fitch) - Sara DeBerry (EDIS, 2011)
Neodiprion lecontei is an important defoliator of commercially grown pine, as the preferred feeding conditions for sawfly larvae are enhanced in monocultures of shortleaf, loblolly, and slash pine, all of which are commonly cultivated in the southern United States. Learn more with this 5-page fact sheet written by Sara DeBerry and published by the UF Department of Entomology and Nematology, January 2011.